Alternatively spliced short and long isoforms of adaptor protein intersectin 1 form complexes in mammalian cells - Gubar, O.S.; Kropyvko, S.V.; Tsyba, L.O.; Gasman, S.; Rynditch, A.V. (Вiopolymers and Cell, 2012)
Intersectin 1 (ITSN1) is an adaptor protein involved in membrane trafficking and cell signaling. Long and short
isoforms of ITSN1 (ITSN1-L and ITSN1-S) are produced by alternative splicing. The aim of our study was to
investigate whether ITSN1-L and ITSN1-S could interact in mammalian cells. Methods. During this study we
employed immunoprecipitation and confocal microscopy. Results. We have shown that endogenous ITSN1-S coprecipitates with overexpressed ITSN1-L in PC12, 293 and 293T cells. Long and short isoforms of ITSN1 also colocalize in 293T cells. Conclusions. ITSN1-L and ITSN1-S form complexes in mammalian cells.
Keywords: ITSN1, alternatively spliced isoforms, adaptor/scaffold proteins. Інтерсетин 1 (ITSN1) – адатоний білок, залучений до мембранного транспорту та передачі клітинних сигналів. Довга і коротка ізоформи ITSN1 (ITSN1-L і ITSN1-S) утворюються в результаті альтернативного сплайсингу. Метою роботи було встановити, чи можуть ITSN1-L і ITSN1-S взаємодіяти в клітинах ссавців. Методи. Використано методи імунопреципітації та конфокальної мікроскопії. Результати. Показано, що ендогенний ITSN1- S копреципітується з надекспресованим ITSN1-L у клітинах PC12, 293 і 293T. Довга і коротка ізоформи ITSN1 також колокалізуються у клітинах 293T. Висновки. ITSN1-L і ITSN1-S формують комплекси в клітинах ссавців. Ключові слова: ITSN1, альтернативно сплайсовані ізоформи, адапторні білки. Интерсектин 1 (ITSN1) – адапторный белок, участвующий в мембранном транспорте и передаче клеточных сигналов. Длинная и короткая изоформы ITSN1 (ITSN1-L и ITSN1-S) образуются вследствие альтернативного сплайсинга. Целью исследования было выяснить, могут ли ITSN1-L и ITSN1-S взаимодействовать в клетках млекопитающих. Методы. Использованы методы иммунопреципитации и конфокальной микроскопии. Результаты. Показано, что эндогенный ITSN1-S копреципитируется со сверхэкпрессированным ITSN1-L в клетках PC12, 293 и 293T. Длинная и короткая изоформы ITSN1 так же колокализуются в клетках 293T. Выводы. ITSN1-L и ITSN1-S формируют комплексы в клетках млекопитающих. Ключевые слова: ITSN1, альтернативно сплайсированные изоформы, адапторные белки.